Climate change and dryland wheat systems in the US Pacific Northwest. (January 2018) - Karimi, T.; Stöckle, C.O.; Higgins, S.; Nelson, R.
Abstract: A regional assessment of baseline (1980–2010) and future (2015–2085) yields of dryland wheat-based cropping systems in the US Inland Pacific Northwest (IPNW) was conducted. The computer simulation-based assessment was done using CropSyst, a cropping systems simulation model, and projected daily weather data downscaled to a 4 × 4 km grid using 12 general circulation models (GCMs) for two atmospheric CO2 representative concentration pathways (RCP 4.5 and RCP 8.5). The study region was divided into 3 agro-ecological zones (AEZs): continuous cropping (CC), continuous cropping-fallow transition (CCF), and crop-fallow (CF), with the following typical rotations assigned to the zones: winter wheat (WW) – summer fallow (SF) (CF zone), WW – spring wheat (SW) – SF (CCF zone), and WW – SW – spring pea (CC zone). By the 2070s (2065–2085), precipitation in the IPNW is projected to increase by about 8 and 12% compared to the baseline period under RCP 4.5 and 8.5, respectively. Mean temperature during the WW growing season will increase about 1.5 and 2.3 °C under RCP 4.5 and 8.5, respectively, but will not change noticeably during the SW growing season due to the adaptive early planting used in this study. Concurrently, atmospheric CO2 concentration will increase from today's average of ~ 400 ppm to 532 ppm to 801 ppm by 2085 depending on future emissions of greenhouse gases. Soil water-crop growth interactions, which show large variation across the region, will modulate crop responses to these changing conditions, with our results showing an overall increase in yield across the IPNW. By the 2070s, the mean ratio of future to baseline WW yield will range from 1.29 to 1.35 under RCP 4.5 and from 1.41 to 1.64 under RCP 8.5 depending on the AEZ. The mean yield ratio for SW across AEZs will range from 1.38 to 1.53 under RCP 4.5 and 1.54 to 1.91 under RCP 8.5. Given substantial climatic heterogeneity in the region, these gains will not be distributed equally across the region or within AEZs, and overall they will not be shared equally by all growers. Highlights: CropSyst, 12 General Circulation Models, and two atmospheric CO2 representative concentration pathways were used. Earlier planting of spring wheat in the future was accounted for. Transpiration-use efficiency will increase due to the CO2 fertilization effect. Winter and spring wheat yields will increase 29–64% and 38–91% by 2085 depending on climatic region and CO2 concentration. Increasing CO2 will counterbalance warming until about midcentury and increase yields, but the effect will decrease later. Future larger productivity will not be distributed equally within the US Inland Pacific Northwest. Technology changes, better adapted cultivars, and pest and disease effects were not considered.